Hubungan Antara Pengetahuan Tentang Posyandu Dengan Keaktifan Ibu Dalam Kegiatan Posyandu Di Desa Simo Kecamatan Kradenan Kabupaten Grobogan - Mudawamah, Hanik, Abi Muhlisin, SKM., M.Kep (2017)
This research aims to know the relationship between the knowledge about posyandu with the liveliness of the mother in the village of posyandu activity Sub Simo Kradenan Grobogan. Type of this research is a descriptive correlative, using the approach of cross sectional Study was carried out in the village of Kradenan Subdistrict Simo Posyandu Grobogan, in February-March 2017. Based on results of the study showed the levels of knowledge of the mother who had a toddler about posyandu in posyandu Village Simo Subdistrict in Grobogan Kradenan category good levels of liveliness mother who had a toddler in activities at the village of toddler posyandu Simo Grobogan category is not active there is the mother of knowledge about posyandu's relationship with the liveliness of the mother in the village of posyandu activity Sub Simo Kradenan Grobogan as evidenced by the value of the sig (0.001) < 0.05.